Neuroarchitecture and its relationship with the architectural quality of educational spaces - Pérez-Ferré, Antonella Abigail de los Angeles; Loyola-Jesús, Almendra María; Cruzado-Palacios, María Delia (LACCEI, 2025)
Neuroarchitecture, as an interdisciplinary approach, studies the relationship between the built environment and the cognitive, emotional and behavioural processes of its users. In the educational context, the architectural quality of spaces directly influences well-being, concentration and learning. This study analyses this relationship at the Cristo Jesús School, Nuevo Chimbote, using a mixed approach. From a qualitative perspective, observation sheets are used to assess spatial conditions and interviews to identify deficiencies in educational design. At a quantitative level, the chi-square statistical test allows significant correlations to be established between Neuroarchitecture and architectural quality. The research, with a correlational scope and based on a case study, uses observation and survey techniques. The results show that the relationship between Neuroarchitecture and architectural quality is significant, highlighting the importance of optimising educational spaces to improve the user experience. This emphasizes the need to incorporate design strategies that favor comfort and academic performance, promoting more stimulating and functional environments for students and teachers.